Reading Utopia in the Reformation of Punishment. (2019) - Ritger, Matthew
Abstract : Recent scholarship on the first English translation of Thomas More's "Utopia" has asked how its publication in the 1550s fits with the larger agenda of Protestant Reformers who promoted the book alongside their other civic projects. This article argues that the initiatives of greatest relevance were the new house of correction at Bridewell (est. 1553–57) and the infamous Vagrancy Act of 1547–49, which failed to introduce slavery as a punishment in English law. Evidence of user interactions with the 1550s editions, including indexing, annotation, commonplacing, and quotation, helps to analyze how the text's complicated ideas about penal labor were received and reemphasized by early English readers.